A taxonomic review of Microserica Brenske, 1894 from continental Asia (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk; Liu, Wangang; Lukic, Daniel; Bai, Ming (Zootaxa, 2023)
The current paper gives an overview of the species of continental Asia so far assigned to the genus Microserica Brenske, 1894. Moronoserica Ahrens, Lukic & Liu, new genus, and Gastroserica (Helioserica Ahrens, Lukic & Liu, new subgenus), and 33 new species are described: Gastroserica bannok Ahrens, Lukic & Liu, new species, G. fumaria Ahrens, Lukic & Liu, new species, G. ivoi Ahrens, Lukic & Liu, new species, G. loei Ahrens, Lukic & Liu, new species, G. lucidomarginalis Ahrens, Lukic & Liu, new species, G. phukradung Ahrens, Lukic & Liu, new species, G. piceocoerulea Ahrens, Lukic & Liu, new species, G. rubropicea Ahrens, Lukic & Liu, new species, G. simaoensis Ahrens, Lukic & Liu, new species, G. yuebaensis Ahrens, Lukic & Liu, new species, Microserica allovarians Ahrens, Lukic & Liu, new species, Mic. banlaoana Ahrens, Lukic & Liu, new species, Mic. caiyangheana Ahrens, Lukic & Liu, new species, Mic. chaiyaphum Ahrens, Lukic & Liu, new species, Mic. cucphuong Ahrens, Lukic & Liu, new species, Mic. ferestictica Ahrens, Lukic & Liu, new species, Mic. hieroglyphica Ahrens, Lukic & Liu, new species, Mic. multipunctata Ahrens, Lukic & Liu, new species, Mic. namnao Ahrens, Lukic & Liu, new species, Mic. neosimplex Ahrens, Lukic & Liu, new species, Mic. parasimplex Ahrens, Lukic & Liu, new species, Mic. paravicula Ahrens, Lukic & Liu, new species, Mic. planiforceps Ahrens, Lukic & Liu, new species, Mic. viengvai Ahrens, Lukic & Liu, new species, Mic. vinden Ahrens, Lukic & Liu, new species, Mic. vipinglangensis Ahrens, Lukic & Liu, new species, Moronoserica banmethout Ahrens, Lukic & Liu, new species, Mor. renong Ahrens, Lukic & Liu, new species, Mor. squamulatoides Ahrens, Lukic & Liu, new species, Mor. songbae Ahrens, Lukic & Liu, new species, Mor. thungyai Ahrens, Lukic & Liu, new species, Oxyserica bifascipennis Ahrens, Lukic & Liu, new species, O. serena Ahrens, Lukic & Liu, new species. The revision results in 39 new combinations: Gastroserica bisignata (Nomura, 1974) new combination, G. cognata (Frey, 1972) new combination, G. dohertyi (Ahrens & Fabrizi, 2009) new combination, G. hiulca (Brenske, 1897) new combination, G. lucens (Ahrens & Fabrizi, 2009) new combination, G. nitidipyga (Nomura, 1974) new combination, G. quateorum (Frey, 1972) new combination, G. roingensis (Fabrizi & Ahrens, 2016) new combination, G. varians (Moser, 1915) new combination, Microserica avicula (Arrow, 1946) new combination, Mic. costisquamosa (Ahrens, Fabrizi & Liu, 2019) new combination, Mic. septemfoliata (Frey, 1972) new combination, Moronoserica banvaneue (Bohacz & Ahrens, 2020) new combination, Mor. crenatostriata (Ahrens, 2004) new combination, Mor. geberbauer (Ahrens, 2004) new combination, Mor. ginae (Bohacz & Ahrens, 2020) new combination, Mor. helferi (Bohacz & Ahrens, 2020) new combination, Mor. lineata (Moser, 1915) new combination, Mor. squamulata (Moser, 1915) new combination, Mor. tenasserimensis (Bohacz & Ahrens, 2020) new combination, Mor. ventrosa (Bohacz & Ahrens, 2020) new combination, Oxyserica arunensis (Ahrens, 1998) new combination, O. bhutanensis (Frey, 1975) new combination, O. cechovskyi (Ahrens, 1999) new combination, O. diversicornis (Moser, 1915) new combination, O. elegans (Frey, 1975) new combination, O. gandakiensis (Ahrens, 1998) new combination, O. hispidula (Frey, 1975) new combination, O. interrogator (Arrow, 1946) new combination, O. marginata (Brenske, 1896) new combination, O. martensi (Ahrens, 1998) new combination, O. myagdiana (Ahrens, 1998) new combination, O. nigropicta (Fairmaire, 1891) new combination, O. pedongensis (Ahrens, 1998) new combination, O. pruinosa (Hope, 1831) new combination, O. schawalleri (Ahrens, 1998) new combination, O. schulzei (Ahrens, 1998) new combination, O. steelei (Ahrens, 2004) new combination, O. truncata (Brenske, 1898) new combination. Lectotypes were designated of Microserica hiulca Brenske, 1897 and Serica nigropicta Fairmaire, 1891. A checklist and key to genera, species groups, and species is given, the diagnostic characters of the newly revised taxa and their distribution is illustrated.